Caring for vulnerable life in Pope Francis: Bioethics and Pastoral Health Care - Giménez Rodríguez, Carlos (Razón y fe, 2022)
Pope Francis proposes a complete change of references that implies moving from specialized and unrelated ministries, including health ministry, to the understanding of the christian mission as the care of vulnerable life. Vulnerable life is a concept that ranges from dependent and old life to life on planet earth, or the life of the unborn. The article starts from the concept of health ministry that the pontiff manages to show that it is integrated into the broad and inclusive framework of care for vulnerable life. It is a holistic and all-encompassing framework that allows to integrate all the ministries and give an account of all Christian life and mission as self-sacrificing love, understood as the kenotic care of the vulnerability of life.